Analisis Pengaruh Kualitas Pelayanan Room Attendant Terhadap Kepuasan Pelanggan Pada Masa Tatanan Normal Baru Di Hotel The Westin Jakarta - Muhammad Ridwan; Bryantanov Hariana (Jurnal Sains Terapan Pariwisata, 2020)
During the COVID-19 pandemic to date, the hotel industry has been affected. Guest visits have experienced a very erratic decline. Guests staying overnight must follow a number of health protocols determined by the Government, in particular the guarantee of room cleanliness.The purpose of this study is to determine the customer satisfaction with the quality of room attendant services and to explain the factors that affect room attendant services. The method used in this study is a quantitative descriptive method used to describe customer satisfaction with room attendant services. This study uses a quantitative approach, which means the research is carried out by obtaining data in the form of numbers or qualitative data that is numbered. Data was obtained from a checklist of questionnaires to 65 guests who had stayed at The Westin Jakarta hotel. Based on this, the quality of the room attendant section at The Westin Jakarta Hotel is expected to improve and maintain service quality in increasing customer satisfaction, especially during the new normal period.